Public Satisfaction Index Towards The Quality Of Bandung City's Satpol PP Services - Yaya Mulyana A Azis; Ediyanto, Ediyanto; Angeli Putri; Revianti, Revianti; Amanda Oktatiani (Sean Institute, 2024)
Public services by government officials today still have many weaknesses so that they cannot meet the quality expected by the community. The government as a provider of public services is responsible and continues to strive to provide the best service to the community. The low quality of public services provided by government officials has become a bad image of the government among the community. Customer satisfaction is a function of the difference between perceived performance and customer expectations using one of the company's performance levels. The Public Satisfaction Index (PSI) is data and information about the level of public satisfaction obtained from quantitative and qualitative measurements of public opinion in obtaining services from public service providers by comparing their expectations and needs. The implications of good or bad service quality depend on the ability of the service provider to consistently meet customer expectations. Quality provides a special impetus for customers to establish long-term mutually beneficial relationships with the company. Consumer satisfaction is the difference between what consumers expect (expected value) and the situation given by the company in an effort to meet consumer expectations. Basically, consumer satisfaction is a condition where consumer needs, desires, and expectations can be met through products consumed or services received.